2005
DOI: 10.1017/s0007123405000165
|View full text |Cite
|
Sign up to set email alerts
|

The Population Ecology of Interest Group Death: Gay and Lesbian Rights Interest Groups in the United States, 1945–98

Abstract: An event-history analysis of the disbandings of nationally active gay and lesbian rights advocacy groups in the United States for the period 1945-98 is presented. Specifically, the hypothesis (which comes from population-ecology theory) is tested that the survival prospects of gay and lesbian rights interest groups are related non-monotonically to the number of groups in the population (i.e., density). The statistical analyses presented support the hypothesis: as density rises from near zero to high, the death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(58 citation statements)
references
References 2 publications
0
50
1
1
Order By: Relevance
“…This pattern has been reproduced in studies of labor unions (Hannan and Freeman, 1988) and gay and lesbian groups (Nownes and Lipinski, 2005). However, research on voluntary organizations has not always corroborated these results.…”
Section: Deterministic Factorsmentioning
confidence: 94%
See 2 more Smart Citations
“…This pattern has been reproduced in studies of labor unions (Hannan and Freeman, 1988) and gay and lesbian groups (Nownes and Lipinski, 2005). However, research on voluntary organizations has not always corroborated these results.…”
Section: Deterministic Factorsmentioning
confidence: 94%
“…Later it was demonstrated that the liability of newness is often really a liability of adolescence (Bruderl and Schussler, 1990;Fichman and Levinthal, 1991;Nownes and Lipinski, 2005). The personal or financial assets that people have invested in the organization make them reluctant to give up right away.…”
Section: Deterministic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is an important caveat here. Even in cases with near infinite resources, at some point the number of interest organizations will stop growing because the marginal utility of ever more specialized interest organizations declines with density (Lowery andGray 1995, Nownes andLipinski 2005). In other words, the growth of the number of organizations depends on the pre-existing density of organizations in an economic sector.…”
Section: The Supply Of Interest Organizationsmentioning
confidence: 99%
“…The design of each of the abovementioned studies guarantees some variation in the context in which groups operate. In the examples cited, this variation is at the level of the policy issue or legislative proposal, but there are also large-n, explanatory studies with cross-country (Rasmussen 2010) or time series designs (Fisker 2013, Nownes& Lipinski 2005. The large majority of studies do not choose a country comparison.…”
Section: Introductionmentioning
confidence: 99%